Knowledge of female undergraduate students on breast cancer and breast self-examination in Klang Valley, Malaysia - Akhtari-Zavare, Mehrnoosh; Abd Latiff, Latiffah; Juni, Muhamad Hanafiah; Md Said, Salmiah; Ismail, Irmi Zarina (Medknow Publications and Media, 2015)
BACKGROUND: In Malaysia, breast cancer is the first cancer among females regardness of race. AIM: The purpose of this study was to identify the knowledge and BSE practice among undergraduate female students at four public universities in Klang Valley, Malaysia. MATERIALS AND METHODS: This cross-sectional study was conducted among 820 undergraduate female students using a self-administered questionnaire covering socio-demographic data, knowledge of breast cancer and BSE practice. RESULTS: The mean age of the respondents was 21.7±1.2 years. The majority of them were single (96.8%), Malay (91.9%) and 16.5% of respondents had a family history of breast cancer. This study showed low level of knowledge on breast cancer and breast self-examination among participants. Only 19.6% participants were performing BSE regularly. Knowledge of breast self-examination was significantly associated with BSE practice (p=0.00). Also, there were significant associations between performing BSE with age, marital status and being trained by a doctor for doing BSE (p<0.05). CONCLUSIONS: Our findings showed that the rate of BSE practice and knowledge of breast cancer is inadequate among young Malaysian females. A public health education program is essential to improve breast cancer prevention among this group.